Nueva lectura de una defixio de Selinunte (SEG XXVII 1115) - Nieto Ibáñez, Jesús María; López Jimeno, María del Amor (1989)
In 1976 A. Brugnone published a series of defixiones from Selinous that herself dated as far back as the sixth century B.C., establishing them as the most ancient series of curses known. In this article we try to correct the reading of one of them because we consider that it does not follow the Dorian dialect in which it was written. We offer a new version that is also supported by some parallelism with existing similar texts.
Keywords: Dialéctica